Uv Spectrophotometric Method For Simultaneous Estimation Of Lansoprazole (Lsp) And Domperidone (Dpd) In Combined Pharmaceutical Formulation - Yadav , Satish Kumar; Bhausaheb , Ghawate Vilas (Journal of Neonatal Surgery, 2025)
The scope of developing and validating a method is to ensure a suitable strategy for particular analysis which is more specific, reliable, accurate and precise. To develop and validate an accurate, precise, reliable and cost-effective stability indicating UV method for simultaneous estimation of Lansoprazole (LSP) and Domperidone (DPD) in combined pharmaceutical formulation. Lansoprazole (LSP) is used as management of acidity and nausea and vomiting. The wavelength of maximum absorbance for Lansoprazole (LSP) and Domperidone (DPD) was 287.2 nm and 301 nm respectively. The UV method used for analysis was Q-Absorption ratio method; overlain spectra show the isosbestic point at 253nm. The linear regression analysis data for the calibration plots showed good linear relationship with R2=0.9934 and 0.9919 for Lansoprazole (LSP) and Domperidone (DPD) respectively at the concentration range of 2–20 µg/mL for Lansoprazole (LSP) and 2–20 µg/mL μg/mL for Domperidone (DPD). The method was validated for accuracy, precision, specificity and robustness. The proposed developed stability indicating method can be applied for identification and quantitative determination of Lansoprazole (LSP) and Domperidone (DPD) in drug formulation